Validity of Queen's College step test for use with young Indian men. Issue 3 (21st May 2004) - Chatterjee, S; Chatterjee, P; Mukherjee, P S; Bandyopadhyay, A
Abstract : Objectives: To assess the suitability of the Queen's College step test (QCT) to predict maximum oxygen uptake in Indian men. Methods: Thirty sedentary male university students from West Bengal, India, with the same socioeconomic background and mean (SD) age, height, and weight of 22.6 (0.2) years, 166.4 (0.5) cm, and 53.8 (0.2) kg, respectively, were randomly sampled from University of Calcutta. VO2 max of each participant was determined by direct procedure involving incremental bicycle exercise and also by applying indirect QCT method with a gap of 4 days between the tests. Results: The difference between the mean (SD) VO2 max values directly measured (VO2 max = 39.8 (1.03) ml/min/kg body mass) and indirectly predicted (PVO2 max = 39.3 (1.07) ml/min/kg body mass) was statistically insignificant (p>0.10). PVO2 max and VO2 max values expressed as ml/min/kg body mass corroborated with previous studies in the same laboratory involving the same population, and also exhibited significant statistical correlation ( r  = 0.95, p<0.001) between them. Conclusion: The results suggest that QCT can be applied in the studied population to produce a good estimation of maximum oxygen uptake, especially in the field where large numbers of participants are to be evaluated without a well equipped laboratory.